THE CAPACITY OF MICROTEACHING LESSON STUDY IN PROMOTING TEACHING PRACTICE AND PEDAGOGICAL DEVELOPMENT - Asman, Hamid (Jurnal Pendidikan Bahasa, 2016)
The purposes of this research are to investigate the implementation of Microteaching lesson study in promoting teaching practice and pedagogical development of the pre-service teachers in English Education Study Program. Method used in this research was case study. This case study involved 9 students of English Education Study Program who take Microteaching class. Data of this research was taken from interview. The finding of this research revealed that microteaching lesson study allowed participative discussion about learning and teaching and opportunities for a collaborative approach in which both lecturer and student-teachers focused on the improvement of pedagogy and teaching practice. It is found that microteaching lesson study leads to the pedagogical development as well as collaborative opportunity to explore the complex system of classroom-oriented processes. Seeing teacher development in relation to an emergent holistic concept of pedagogic development implies a comprehensive dynamic vision of how teaching quality develops.Keywords: microteaching lesson study, pre-service teachers, teaching practice and pedagogical development.